Supervisory control of operation of a cogeneration plant using fuzzy logic - Vivek Pandurangan; Om P. Malik (Institute of Advanced Engineering and Science, 2019)
A fuzzy logic based supervisory controller for the multivariable control problem in the operation of a cogeneration plant is proposed. Results of simulation studies with the proposed controller on a dynamic model of the cogeneration plant show that the plant performs to expectations and tracks the set-points in an optimal manner while maintaining critical plant parameters within limits.